a.)
\(\displaystyle y = 2^{x}\)
\(\displaystyle \log_2(y) = \log_{2}(2^{x})\)
\(\displaystyle \log_{2}(y) = x\)
- What is the next step?
This next example is very clear:
b.)
\(\displaystyle 8 = 2^{x}\)
\(\displaystyle \log_{2}(8) = \log_{2}(2^{x})\)
\(\displaystyle 3 = x\)
\(\displaystyle y = 2^{x}\)
\(\displaystyle \log_2(y) = \log_{2}(2^{x})\)
\(\displaystyle \log_{2}(y) = x\)
This next example is very clear:
b.)
\(\displaystyle 8 = 2^{x}\)
\(\displaystyle \log_{2}(8) = \log_{2}(2^{x})\)
\(\displaystyle 3 = x\)
Last edited: